New Data on Breeding Biology, Ecology, and Population Status of White-Tailed Eagle in Dagestan, Russia - Rinur H. Bekmansurov; Gadzhibek S. Dzhamirzoev; Hadzhaman N. Ismailov; Alim В. Pkhitikov (Пернатые хищники и их охрана)
White-Tailed Eagle (Haliaeetus albicilla) in Dagestan is a nesting sedentary-nomadic, migratory, and wintering species of lowland areas (Pishvanov et al., 1991; Dzhamirzoev, Bukreev, 2009; Bukreev, Dzhamirzoev, 2013; 2020; Dzhamirzoev, Bukreev, 2020). Three nestlings were tagged with GSM/GPS trackers in one nest in the Kizlyar Bay during the research program of the “Dagestansky” Nature Reserve (Bekmansurov et al., 2018).